IDENTIFICATION OF INDONESIAN ETHNOMEDICINAL PLANTS AS POTENTIAL DRUG CANDIDATES FOR ACUTE RESPIRATORY INFECTION USING COMPUTER-AIDED DRUG DESIGN AND SIMRS MODEL - Jackson, James; Tanaya, Davina Nadine; Setiawan, Stefanus (BRIN - Badan Riset dan Inovasi Nasional, 2024)
In 2023, Indonesia’s air quality deteriorated, with its Air Quality Index (AQI) tripling clean air standards, causing health sector losses, including a surge in Acute Respiratory Infection (ARI) cases. One of the ARI treatments is the consumption of cefuroxime, yet it can cause side effects. Indonesia’s floral biodiversity in ethnomedicinal plants can be utilized as a more natural drug candidate for ARI drugs. To determine this, an in silico approach is performed through molecular docking, and Pre-ADMET prediction. Based on the compound selection’s results, lanosterol is the most promising compound, with a binding energy value of -8.11 kcal/mol and an efficiency of 78.81%, while cefuroxime as a reference ligand has a binding energy value of -5.92 kcal/mol with an efficiency of 67.87%. After undergoing compound selection, a time series analysis through the Susceptible Infected Medicine Recovered Susceptible (SIMRS) model is conducted. In this analysis, it is found that cefuroxime and lanosterol require the same amount of time, which is 33 days to restore Indonesia to its pre-ARI outbreak condition, indicating that lanosterol can be used as an alternative drug candidate.